2017
DOI: 10.2485/jhtb.26.417
|View full text |Cite
|
Sign up to set email alerts
|

Histological Comparison of Autogenous and Allogenic Demineralized Dentin Matrix Loaded with Recombinant Human Bone Morphogenetic Protein-2 for Alveolar Bone Repair: A Preliminary Report

Abstract: The goal of investigation is to examine the histological response to recombinant human bone morphogenetic protein-2 (rhBMP-2)-loaded demineralized dentin matrices (DDMs) of different origins. The evaluation site is chosen between the cover screw and gingiva, as the poor blood supply allows it to simulate a heterotopic condition. We hypothesize that the antigenicity and immunogenicity of the carrier allogenic DDMs are low enough to maintain both the biocompatibility of the scaff old and the activity of the load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…In the preliminary human clinical report, the DDM/rhBMP-2 (0.2 mg/ml concentration) exhibited multiple irregularly shaped surfaces infiltrated by activated cells, as well as isolated spaces that filled with infiltrating cells. These spaces were consistent with collagenolytic resor ption with fibroblast infi ltration and were reminiscent of DDM undergoing resorption by multinucleated giant cells 49) .…”
Section: Discussionsupporting
confidence: 61%
“…In the preliminary human clinical report, the DDM/rhBMP-2 (0.2 mg/ml concentration) exhibited multiple irregularly shaped surfaces infiltrated by activated cells, as well as isolated spaces that filled with infiltrating cells. These spaces were consistent with collagenolytic resor ption with fibroblast infi ltration and were reminiscent of DDM undergoing resorption by multinucleated giant cells 49) .…”
Section: Discussionsupporting
confidence: 61%
“…29 In our preliminary clinical report, histological specimens of DDM/rhBMP-2 obtained at the time of second surgery had multiple irregularly shaped surfaces infiltrated by activated cells, as well as isolated spaces that became filled with infiltrating cells. 19 These spaces were consistent with collagenolytic resorption and fibroblast infiltration and were reminiscent of DDM undergoing resorption by multinucleated giant cells. These observations seem consistent with the reports of Ike and Urist 14 and Murata, 15 which showed that as the quantity of induced bone increased after treatment with DDM/rhBMP-2, the resorption and replacement of the dentin matrix (carrier) also increased.…”
Section: Histomorphometric Analysismentioning
confidence: 55%
“…In our preliminary clinical report, histological specimens of DDM/rhBMP‐2 obtained at the time of second surgery had multiple irregularly shaped surfaces infiltrated by activated cells, as well as isolated spaces that became filled with infiltrating cells . These spaces were consistent with collagenolytic resorption and fibroblast infiltration and were reminiscent of DDM undergoing resorption by multinucleated giant cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations